PELATIHAN MINDFULNESS BERBASIS SANDPLAY THERAPY UNTUK MENINGKATKAN KESEJAHTERAAN PADA GURU SEKOLAH DASAR DI KABUPATEN KEBUMEN - Irma Rosalinda Lubis; Lupi Yudhaningrum; Nazir Ultama Anugrah; Khairina Widya Primandari Haryono; Syaiful Arif (Jendela Akademika, 2026)
Teachers’ well-being is a crucial factor that directly influences the quality of teaching and learning processes. However, teachers often experience psychological distress due to heavy workloads, administrative duties, and limited economic welfare. These pressures reduce their motivation and mental health, which negatively impacts educational quality. This community service program aims to implement mindfulness training as an intervention to enhance teachers’ well-being in elementary schools in Kebumen Regency. A total of 105 teachers participated, divided into an experimental group (55 teachers) and a control group (50 teachers). The program used sandplay therapy-based mindfulness training within a quasi-experimental design. Training activities included mindfulness awareness, breathing techniques, emotional regulation, and reflection sessions using sandplay media. The evaluation showed asignificant improvement in well-being among teachers who attended the training (p = 0.019), compared to minor external changes in the control group (p = 0.013). Qualitative reflections also revealed that participants felt calmer, more focused, and more motivated in teaching after the program. The findings confirm that mindfulness training is an effective and low-cost psychological intervention that can be integrated into teacher professional development programs. This program highlights the importance of addressing teachers’ mental health as part of national education quality improvement strategies.